Risk perception and influenza vaccine hesitancy among university students in Saudi Arabia - Alnezary, Faris S.; Alhejaili, Rama A.; Alayashi, Alaa A.; Alnizari, Dina S.; Bin Mirdhah, Nada S.; Alrays, Shaden K.; Alobid, Saad; Alzahrani, Fahad; Fadil, Haifa A.; Alrohily, Waad; Thabit, Abrar K.; Mahmoud, Mansour A.; et al. (Frontiers in Pharmacology, 2026)
IntroductionUniversity campuses are high-risk environments for influenza transmission, yet vaccine coverage among students often remains suboptimal. This study aimed to identify the determinants of vaccine hesitancy among university students in Saudi Arabia using the Health Belief Model (HBM) framework.MethodA cross-sectional study was conducted between January and September 2024. Data were collected via a validated online Arabic questionnaire assessing HBM constructs—susceptibility, severity, benefits, and barriers—alongside sociodemographic variables. Ethical approval was obtained for human participation.ResultsOf the 450 university students surveyed, 62.4% reported encountering significant barriers to vaccination. Despite a high recognition of vaccine benefits (66.7%), this awareness did not correlate with higher intention to vaccinate after adjusting for sociodemographic factors. Students perceiving fewer barriers exhibited substantially higher acceptance rates compared to those perceiving high barriers (60% vs. 27.8%). Furthermore, female students were nearly twice as likely to report moderate barriers (aOR = 1.994) compared to males, while healthcare students were significantly less likely to perceive such obstacles (aOR = 0.654). Students with chronic conditions also demonstrated higher vaccine acceptance (44.1%) compared to their healthy peers (20.2%).ConclusionInfluenza vaccine uptake among Saudi university students is hindered primarily by perceived barriers rather than a lack of awareness regarding vaccine benefits. Public health strategies on campuses should shift focus from simply emphasizing advantages to actively mitigating logistical and misconception-based obstacles, particularly targeting non-healthcare disciplines and female students.